2000
DOI: 10.1067/mva.2000.110344
|View full text |Cite
|
Sign up to set email alerts
|

Free tissue transfer provides durable treatment for large nonhealing venous ulcers

Abstract: Free tissue transfer can provide rapid healing and long-term relief from severe VUs that are unable to be treated with conventional therapy. This technique improves venous hemodynamics, removes all liposclerotic tissue, provides an abundant blood supply, and resolves the tissue-related components of chronic ulceration. Although further work is needed to determine the optimal indications, this technique provides a durable treatment for especially recalcitrant ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 24 publications
1
45
0
4
Order By: Relevance
“…Weinzweig et al also described a 10-year experience using free muscle flaps to reconstruct 24 recalcitrant venous stasis ulcers. 12 After a mean follow-up of 58 months, no recurrent ulcers were identified in the flap territory; however, three patients developed new ulcers on the same leg.…”
Section: A D E B Cmentioning
confidence: 99%
“…Weinzweig et al also described a 10-year experience using free muscle flaps to reconstruct 24 recalcitrant venous stasis ulcers. 12 After a mean follow-up of 58 months, no recurrent ulcers were identified in the flap territory; however, three patients developed new ulcers on the same leg.…”
Section: A D E B Cmentioning
confidence: 99%
“…6 Because of lipodermatosclerosis, some venous ulcers do not heal despite optimal treatment, and 60% of ulcers recur after initial healing. 7 Surgical treatment of these ulcers can be accomplished by removal of ulcer and surrounding lipodermatosclerotic tissue, followed by tissue transfer to close the resulting soft-tissue defect.…”
mentioning
confidence: 99%
“…The results showed that all ulcers were healed, and no recurrent ulcers were identified after a 58-month follow-up. 58 The complications after interventions include infection, superficial or deep vein thrombosis, numbness, paresthesia, ecchymosis, and skin staining. However, the prevalence of significant complications is less than 5 percent.…”
Section: Surgical Interventionmentioning
confidence: 99%